The first larval stage (Zoea i) description of the caridean shrimp ogyrides occidentalis (ortmann, 1893) (alpheoidea: Ogyrididae) reveals congruence with taxonomic status - Pantaleão, João Alberto Farinelli [UNESP] (2021)
A complete and detailed description of the first zoeal stage of Ogyrides occidentalis is provided. Larvae were obtained in the laboratory from a female with embryos collected in Ubatuba, State of São Paulo, Brazil. The morphological characters are compared with previous description of the close related O. alphaerostris. Despite of some similarities (number of appendages, pleonites, and setae on the majority of appendages) substantial differences were found between the two species, as the size of larvae and rostrum and segmentation of some structures (antenna exopod, first maxilliped coxa and basis). However, these differences must be interpreted carefully because larval description of O. alphaerostris was conducted before the proposed standardization for decapod larval morphology descriptions. The present larval description furnished additional information to corroborate the recent resurrection of O. occidentalis and will be useful for future comparative and ecological research.